Spectrophotometric Estimation of Risperidone in Tablets - Jayanna, B. K. (Indian J Pharm Sci, 2014)
A simple, rapid and highly sensitive spectrophotometric method is developed for the determination of risperidone in tablet formulation. The method is based on the oxidation of drug using potassium permanganate in alkaline medium and excess potassium permanganate oxidizes 1,10-phenanthroline Fe(II). The measurement of decrease in absorbance of 1,10-phenanthroline Fe (II) was done at 415 nm. The beer's law is obeyed in the concentration range of 5.0 to 40.0 μg/ml and molar absorptivity is found to be 7.3932 × 10(4) l/mol/cm. The proposed method is well suited for the pharmaceutical formulations.